Public knowledge of early stroke symptoms in the Vilnius region - Atkočiūnas, A.; Mačionytė, M.; Mameniškienė, R. (Neurologijos seminarai, 2023)
Background and aim. Stroke remains one of the most common causes of death and disability in the world. The evident decline in disabling outcomes can be attributed to the increasing use of reperfusion therapies. Stroke recognition and urgent admission of patients to specialized stroke centres after the onset of first stroke symptoms are essential for treatment outcomes. This study aims to assess public stroke awareness and its change since 2019.Methods. An anonymous cross-sectional study involving 300 Vilnius residents was conducted in 2022, the results of which were compared with the data of 502 respondents in 2019. A closed-ended questionnaire was used for the study. Statistical analysis was performed using IBM SPSS software with p
Keywords: stroke; signs; survey; public